As you can see from the image in the picture all the sides of the triangle are equal to each other (25). This means that this is an equilateral triangle.
The definition of an equilateral triangle is:
A triangle that has all sides equal to each other. The angles are also equal to each other. Since it is known that the sum of all the angles of a triangle equals 180, one angle of an equilateral triangle is always 60 degrees ( 180 / 3 = 60).
That means angle B has the measure of 60 degrees
Hope this helped!
~Just a girl in love with Shawn Mendes
Determine the equation of quadratic function represented by the table of value below.
Answer:
A
Step-by-step explanation:
The general rule for the quadratic function is
[tex]y=ax^2+bx+c[/tex]
Use the data from the table:
[tex]y(0)=6\Rightarrow 6=a\cdot 0^2+b\cdot 0+c\\ \\y(1)=4\Rightarrow 4=a\cdot 1^2+b\cdot 1+c\\ \\y(-1)=10\Rightarrow 10=a\cdot (-1)^2+b\cdot (-1)+c[/tex]
We get the system of three equations:
[tex]\left\{\begin{array}{l}c=6\\ \\a+b+c=4\\ \\a-b+c=10\end{array}\right.[/tex]
From the first equation
[tex]c=6,[/tex] then
[tex]\left\{\begin{array}{l}a+b=-2\\ \\a-b=4\end{array}\right.[/tex]
Add these two equations:
[tex]a+b+a-b=-2+4\\ \\2a=2\\ \\a=1[/tex]
So,
[tex]b=-2-a=-2-1=-3[/tex]
The quadratic function is
[tex]y=1\cdot x^2-3x+6\\ \\y=x^2-3x+6[/tex]
What is the area of triangle ACD
Answer:
The area of triangle ACD is 4 centimeters squared.
Step-by-step explanation:
The formula to find the area of a triangle is 1/2 * base * height. The base of this triangle is 2 cm and the height is 4 cm, so you can multiply that and then the answer by half.
Area = 1/2 * 4 * 2
= 1/2 * 8
= 4
Answer: 4 cm squared.
Hope this helped :)
Check the picture below.
PLEASE HELP ME ASAP 25 POINTS !!!!
Answer:
78˚
Step-by-step explanation:
Triangle MNP is congruent to Triangle QST, and so their angle measures are the same.
If you look at the order of the letters in the triangle names, you will notice that angle N lines up with angle S, so that means their angle measures are the same. Therefore if angle N is 78˚, angle S will be 78˚ as well.
Answer:
∠S = 78°
Step-by-step explanation:
Corresponding angles are equal, that is
∠Q = ∠M = 66° and
∠S = ∠N = 78°
Write the sum using summation notation, assuming the suggested pattern continues.
25 + 36 + 49 + 64 + ... + n2 + ...
Answer:
[tex]\sum_{n=5}^{\infty}n^2[/tex]
Step-by-step explanation:
The pattern given is:
25+36+49+64+...+n^2+...
The pattern can be written as
(5)^2+(6)^2+(7)^2+(8)^2+.....+n^2+....
The series is started with 5 and it continues up to infinity.
The summation notation for the given series is:
[tex]\sum_{n=5}^{\infty} n^2[/tex]
n= 1 and goes up to infinity and the series is made up of taking square of n,
The sum using summation notation, assuming the suggested pattern continues is :
[tex]25 + 36 + 49 + 64 + ... + n^2 + ...=\sum_{n=5}^{\infty} n^2[/tex]
Step-by-step explanation:We are given a series of numbers as
25 + 36 + 49 + 64 + ... + n^2 + ...
To write the sum using summation notation means we need to express this series in terms of a general n such that there is a whole summation expressing this series.
Here we see that each of the numbers could be expressed as follows:
[tex]25=5^2\\\\36=6^2\\\\49=7^2\\\\64=8^2[/tex]
and so on.
i.e. the series starts by taking the square of 5 then of 6 then 7 and so on.
and the series goes to infinity.
Hence, the summation notation will be given by:
[tex]25 + 36 + 49 + 64 + ... + n^2 + ...=\sum_{n=5}^{\infty} n^2[/tex]
What is the base if the rate is 41% on the percentage is 83
Answer:
202,44
Step-by-step explanation:
We know that 41% of a number is 83, and we need to find the base number. To do so, we're going to use the rule of three, as follows:
If 83 represents -----------------------------> 41% of a number
X <------------------------------ 100% of a number
Then:
X = (100 * 83)/41 = 202,44
Therefore, the base number is: 202,44 ✅
In a soccer team, 1/3 of the players ride a bike to practice, 25% walk to practice and the remaining 15 players are driven by their parents. How many players are there in the team?
a. 42 b. 36 c. 30 d. 21
Final answer:
By setting up an equation based on the proportions of players who bike, walk, and are driven to practice, and solving for the total number of players, it is determined that there are 36 players on the soccer team.
Explanation:
To determine the total number of players in the soccer team, we can use the information given about the fractions of players commuting by different modes of transportation and the number of players who are driven by their parents.
We know that 1/3 of the players ride a bike, 25% (which is equivalent to 1/4) walk, and the remaining 15 players are driven by their parents.
Let's denote the total number of players as T. The parts of the team that ride a bike and walk can be represented as T/3 and T/4, respectively. The remaining players are represented by the number 15.
Since these components add up to the whole team, we can write the equation:
T/3 + T/4 + 15 = T
To solve for T, we first need to find a common denominator, which is 12 in this case. The equation becomes:
4T/12 + 3T/12 + 15 = T
Combining the T terms gives us:
7T/12 + 15 = T
This simplifies to:
7T/12 = T - 15
Multiplying both sides of the equation by 12 to eliminate the fraction gives us:
7T = 12T - 180
Subtracting 7T from both sides results in:
5T = 180
Dividing both sides by 5, we finally get:
T = 36
Therefore, there are 36 players in the soccer team.
Use the quadratic expression 15x2+14x−16 to answer the questions.
A: Which statement describes the correct method to factor the quadratic expression?
B: What are the factors of the quadratic expression?
Select one answer for question A, and select two answers for question B.
A: This quadratic expression can be factored by using the difference of squares pattern.
A: This quadratic expression can be factored by finding the correct pair of binomial factors.
A: This quadratic expression can be factored by using the perfect square trinomial pattern.
B: (3x+4)
B: (3x−2)
B: (5x+8)
B: (5x+4)
B: (5x−4)
B: (3x+4)
Answer:
A: second one or middle choice
B: (5x + 8)(3x - 2)
Step-by-step explanation:
First question (A)
It is a trinomial. You can't use the difference of squares on it. The difference of squares have two terms as an answer.
It is not a perfect square. 15 is not a perfect square and c would have to be positive not minus to even think about using a perfect square.
So the A answer is the second one. You need two different binomials to factor this.
Second Question
You could try all the possible pairings and solve them by brute force.
The are five choices the go with the first one (3x + 4). Eventually you would get the answer, you would have to try 5 + 4 + 3 + 2 + 1 = 15 attempts.
There must be a shorter way.
14 means that the expressions are fairly far apart. This was just luck on my part. There is no logic. 8 and 2 for 16 are fairly far apart.
(5x + 8)(3x - 2)
The middle term is 8*3x - 2*5x = 14x and that looks like the answer.
:
Allen is building birdhouses that require 12-ft-long boards. How many pieces that are exactly 12ft long can be made from a board that is 814ft long?
Answer:
67 boards
Step-by-step explanation:
Given :
Total board length = 814 ft
Each board must be exactly 12 feet
Number of 12 ft boards which can be cut from 814 feet,
= 814 ÷ 12
= 67.83 boards
But because the question requires boards which are exactly 12 feet long, so we have to round down to the nearest whole number
hence 67.83 boards rounded down to the nearest whole board becomes 67 boards.
can 1,2,5 be the lengths of a triangle
Answer:
No
Step-by-step explanation:
In order to be the lengths of sides of a triangle:
Sum of any two side lengths must always be greater than the third side.
Here,
[tex]1 + 2 = 3 \ngtr 5 \\ [/tex]
Hence, 1, 2, 5 can't be lengths of triangle.
Write
as a percentage.
For this case we must write as a percentage the following expression:
[tex]\frac {21} {25}[/tex]
Dividing we have to:
[tex]\frac {21} {25} = 0.84[/tex]
Now we multiply by 100%. So:
[tex]0.84 * 100 =[/tex]
We run the decimal two spaces to the right, finally we have:
84%
Answer:
84%
[tex]\text{Hey there!}[/tex]
[tex]\text{Percentages usually run out of 100}[/tex]
[tex]\dfrac{21}{25}\ = \ 21\div25\ = \ 0.84[/tex]
[tex]\huge\text{Decimal form: 0.84}[/tex]
[tex]\text{Remember what I said, percentages run out 100. ( e.g. x * 100)}[/tex]
[tex]\text{0.84\% }\times\text{ 100 = 84\%}[/tex]
[tex]\boxed{\boxed{\huge\text{Answer: 84\%}}}\huge\checkmark[/tex]
[tex]\text{Good luck on your assignment and enjoy your day!}[/tex]
~[tex]\frak{LoveYourselfFirst:)}[/tex]
Find x.
A.8
B.10
C.10.5
D.12
Answer:
10
Step-by-step explanation:
Setup a proportional for similar triangles when finding lengths.
We have FG~MN and GH~N0.
Corresponding sides of similar triangles are proportional.
[tex]\frac{FG}{MN}=\frac{GH}{NO}[/tex]
[tex]\frac{6}{x}=\frac{9}{15}[/tex]
Cross-multiply:
[tex]9x=6(15)[/tex]
Simplify right hand side:
[tex]9x=90[/tex]
Divide both sides by 9:
[tex]x=\frac{90}{9}[/tex]
Simplify right hand side:
[tex]x=10[/tex]
Cut 63 cm stick into two pieces in such a way that the first piece is 7 less than the second one. Let x be the second one.
Answer:
We have divided the bar into two parts. For example, x and y.
Step-by-step explanation:
So, we have
63cm=x+y (1)
But one of those parts is 7 centimeters smaller than the other.We take y as the smallest part.Then:
y=x-7cm (2)
we replace this information in the first equation
63cm=x+(x-7cm)
63cm=x+x-7cm
7 goes to add to the other side
63cm+7cm=2x
70cm=2x
2 goes to divide to the other side
35cm=x
from the second equation we have
y=x-7cm
y=35cm-7cm=28cm
Finally
x=35cm
y=28cm
x+y=35cm+28cm=63cm
help asap pls
there is a 90% chance that a person eats dinner, a 60% chance a person eats dessert, and 50% chance the person will eat dinner and dessert. which of the following is true
Answer:
Eating dinner and eating dessert are dependent events because
P(dinner) . P(dessert) = 0.9 × 0.6 = 0.54 which is not equal to
P(dinner and desert) = 0.5 ⇒ answer A
Step-by-step explanation:
* Lets study the meaning independent and dependent probability
- Two events are independent if the result of the second event is not
affected by the result of the first event
- If A and B are independent events, the probability of both events
is the product of the probabilities of the both events
- P (A and B) = P(A) · P(B)
* Lets solve the question
∵ There is a 90% chance that a person eats dinner
∴ P(eating dinner) = 90/100 = 0.9
∵ There is a 60% chance a person eats dessert
∴ P(eating dessert) = 60/100 = 0.6
- If eating dinner and dating dessert are independent events, then
probability of both events is the product of the probabilities of the
both events
∵ P(eating dinner and dessert) = P(eating dinner) . P(eating dessert)
∴ P(eating dinner and dessert) = 0.9 × 0.6 = 0.54
∵ There is a 50% chance the person will eat dinner and dessert
∴ P(eating dinner and dessert) = 50/100 = 0.5
∵ P(eating dinner and dessert) ≠ P(eating dinner) . P(eating dessert)
∴ Eating dinner and eating dessert are dependent events because
P(dinner) . P(dessert) = 0.9 × 0.6 = 0.54 which is not equal to
P(dinner and desert) = 0.5
Nick mowed about 3/5 of the school lawn yesterday. The mowed another 1/4 of the remaining portion of the lawn this morning. How much is left to mow?
A. 1/4
B.2/5
C.3/5
D.3/4
E.19/20
Answer:
1/4
Step-by-step explanation:
3/5 x 1/4 = 3/20
3/20 + 2/5 = 3/4
1 - 3/4 = 1/4
so the answer is A
what is y=20^x in log
[tex]y=20^x\Longleftrightarrow x=\log_{20}y[/tex]
Find the distance from the point (8, 4) to the line y =
x+ 2.
Answer:
The distance is [tex]3\sqrt{2}\ units[/tex]
Step-by-step explanation:
step 1
Find the slope of the give line
we have
y=x+2
so
the slope m is equal to
m=1
step 2
Find the slope of the perpendicular line to the given line
Remember that
If two lines are perpendicular, then their slopes are opposite reciprocal of each other
so
we have
m=1 -----> slope of the given line
therefore
The slope of the perpendicular line is equal to
m=-1
step 3
With m=-1 and the point (8,4) find the equation of the line
y-y1=m(x-x1)
substitute
y-4=-(x-8)
y=-x+8+4
y=-x+12
step 4
Find the intersection point lines y=x+2 and y=-x+12
y=x+2 -----> equation A
y=-x+12 ----> equation B
Adds equation A and equation B
y+y=2+12
2y=14
y=7
Find the value of x
y=x+2 -----> 7=x+2 -----> x=5
The intersection point is (5,7)
step 5
Find the distance between the point (8,4) and (5,7)
we know that
The distance from the point (8,4) to the line y=x+2 is equal to the distance from the point (8,4) to the point (5,7)
Find the distance AB
the formula to calculate the distance between two points is equal to
[tex]d=\sqrt{(y2-y1)^{2}+(x2-x1)^{2}}[/tex]
substitute
[tex]d=\sqrt{(7-4)^{2}+(5-8)^{2}}[/tex]
[tex]d=\sqrt{(3)^{2}+(-3)^{2}}[/tex]
[tex]d=\sqrt{18}[/tex]
[tex]d=3\sqrt{2}\ units[/tex]
see the attached figure to better understand the problem
(used parentheses due to "forbidden language")
The figure Shows triangle ABC with medians (A F), BD, and CE. Segment (A F) is extended to H in such a way that segment GH is congruent to segment AG.
Which conclusion can be made based on the given conditions?
A) Segment GF is congruent to segment EG
B) Segment GF is half the length of segment EB
C) Segment GD is congruent to segment EG
D) Segment GD is half the length of segment HC
Answer:
Segment GD is half the length of segment HC ⇒ answer D
Step-by-step explanation:
* Look to the attached file
Answer: D) Segment GD is half the length of segment HC
Which equation can be used to find the volume of a sphere that has a radius of 9 inches
The volume of a sphere that has a radius of 9 inches is 3053.63in³.
V≈3053.63in³
V=4
3πr3=4
3·π·93≈3053.62806in³
Answer:
Therefore, C ) [tex]\frac{4*pi}{3} (9)^{3}[/tex].
Step-by-step explanation:
Given : A sphere that has a radius of 9 inches.
To find : Which equation can be used to find the volume of a sphere.
Solution: We have given
radius of sphere = 9 inches.
Volume of sphere = [tex]\frac{4*pi}{3} (radius)^{3}[/tex].
Plug the valu radius = 9 inches .
Volume of sphere = [tex]\frac{4*pi}{3} (9)^{3}[/tex].
Then equation c is correct answere.
Therefore, C ) [tex]\frac{4*pi}{3} (9)^{3}[/tex].
What is the length of BC in the right triangle below?
By the Pythagorean theorem [tex]a^2+b^2=c^2[/tex], the length of BC [tex]=\sqrt{22^2+120^2}=122[/tex]
Answer: D. 122
Step-by-step explanation: The given polygon is a right triangle, and to calculate any length of any side in a triangle we use Pythagorean Theorem. According to Pythagorean Theorem, the right triangle consists of one hypotenuse that is opposite to the right angle and two other sides that lie at an right angle. From this comes the relationship that always applies to the right triangles, that the area of the square located on the hypotenuse is equal to the sum of the areas of the squares that are located on the other two sides.
Pythagorean Theorem can also be expressed using the equation:
a² + b² = c²
where c is the hypotenuse and a and b are the other two sides of the right triangle.
According to the given triangle, the length of the BC side is the length of the hypotenuse we are looking for, while the lengths of the sides a and b are given, a = 22 and b = 120.
Using Pythagorean Theorem, hypotenuse BC is equal to
c² = a² + b² = 22² + 120² ⇒ c = √(22² + 120²) = √(484 + 14400) = √14884
c = 122
What is the first step in sketching the graph of a rational function?
Answer:
Step-by-step explanation:
Find the x-value that makes the denominator zero. This x = a is the equation of the vertical asymptote. Next, determine the behavior of the function as x increases without bound in either direction. If there is a limiting value, then this y = d is the horizontal asymptote.
Consider the rational function
[tex]f(x)=\frac{P(x)}{Q(x)}[/tex]
We will find the Domain of Rational function first, means those value of rational function for which f(x) is defined, To do this we will evaluate those point first for which, Q(x)=0.
So, The first Step is "Finding Domain of the rational function" as well as the point where function is not defined.
⇒Consider the function
[tex]f(x)=\frac{x-3}{x-2}[/tex]
→Domain of the function is
x-2=0
x=2
=All Real Numbers , except at x=2.
=R- {2}
What is 5|3t+5|=25 and explain
Answer:
t=0 t = -10/3
Step-by-step explanation:
5|3t+5|=25
Divide each side by 5
5|3t+5| /5=25/5
|3t+5|=5
Now to get rid of the absolute value we get two equations, one positive and one negative
3t+5 =5 3t+5 = -5
Subtract 5 from each side
3t+5-5 =5-5 3t+5-5 = -5-5
3t =0 3t = -10
Divide by 3
3t/3 = 0/3 3t/3 = -10/3
t=0 t = -10/3
In circle C, r= 32 units.
What is the area of circle C?
32tt units
6411 units?
O
256T1 units?
1024T units?
Answer:
[tex]1024 {\pi} \: {unit}^{2} [/tex]
units
Answer:
1024 π units square
Step-by-step explanation:
The area of a circle is found by the formula:
Area of Circle = π × [tex]r^{2}[/tex] units square
where r is the radius of a circle
And π is a Greek letter it is a constant whose approximate value is equal to 3.14159 or 22÷7 is also used sometimes.
The area has a square unit this means if the radius is given in meter then Area has unit meter square.
The area can also be determined by diameter whose formula is given by,
Area of Circle = (π ÷ 4 )× (d)² units square
where d is the radius of a circle
Therefore here,
Area of Circle C = π × r × r
= π × 32 × 32 (unit)²
= 1024 π (unit)²
Thus, the last option is correct and first four given option is not correct.
Circumference of a circle is found by 2×π×r, where π and r are same as defined above. This is usually determined when we have to ask to find the length of a given boundary in a question.
and Area is found when
We can also derive the formula of a circle which is given by Archimedes, here we consider the circle as the limit of a sequence of regular polygons. And the Area of a regular polygon can be found by half of a perimeter of the circle (i.e. 2×π×r ) multiplied by the distance from its center to its sides i.e. 1÷2×(2×π×r)×r.
Which of the following represents the factorization of the trinomial below?
x^2 + 13x - 30
Answer:b
Step-by-step explanation:
The factors of the trinomial is option (D) (x+15)(x-2) is the correct answer.
What is factorization?Factorization is the breaking or decomposition of an entity (a number, a matrix, or a polynomial) into a product of another entity, or factors, which when multiplied together give the original number. Factorize an expression involves take out the greatest common factor (GCF) of all the terms.
For the given situation,
The trinomial is x^2 + 13x - 30.
The trinomial can be factored as
⇒ [tex]x^2 + 13x - 30=0[/tex]
⇒ [tex]x^2 + 15x-2x - 30=0[/tex]
⇒ [tex]x(x+15)-2(x+15)=0[/tex]
⇒ [tex](x+15)(x-2)=0[/tex]
Hence we can conclude that the factors of the trinomial is option (D) (x+15)(x-2) is the correct answer.
Learn more about factorization here
https://brainly.com/question/22048687
#SPJ2
Please answer this correctly
Answer:
4/5
Step-by-step explanation:
you need to find the common denominator first, being 15.
then you can do 4/15, 6/15, 8/15, 10/15 making the next one 12/15 or simplified 4/5
Answer:
[tex]\large\boxed{\dfrac{4}{5}}[/tex]
Step-by-step explanation:
Find LCD:
LCM of 15, 5 and 3 is 15
15 = (15)(1)
15 = (5)(3)
15 = (3)(5)
[tex]\dfrac{2}{5}=\dfrac{2\cdot3}{5\cdot3}=\dfrac{6}{15}\\\\\dfrac{2}{3}=\dfrac{2\cdot5}{3\cdot5}=\dfrac{10}{15}[/tex]
Therefore we have:
[tex]\dfrac{4}{15},\ \dfrac{2}{5},\ \dfrac{8}{15},\ \dfrac{2}{3}\to\dfrac{4}{15},\ \dfrac{6}{15},\ \dfrac{8}{15},\ \dfrac{10}{15}[/tex]
Look at the numerators. The next numerator is created from the previous one by adding the number 2.
Therefore the next fraction is equal to
[tex]\dfrac{10+2}{15}=\dfrac{12}{15}=\dfrac{12:3}{15:3}=\dfrac{4}{5}[/tex]
What is the solution to the equation below? Round your answer to two
decimal places.
2^3x=91
Answer:
The solution of the equation is [tex]x=2.169..[/tex]
Step-by-step explanation:
Given : Equation [tex]2^{3x}=91[/tex]
To find : What is the solution to the equation below?
Solution :
Equation [tex]2^{3x}=91[/tex]
Taking log both side,
[tex]\log(2^{3x})=\log(91)[/tex]
Apply logarithmic property, [tex]\log a^x=x\log a[/tex]
[tex]3x\log(2)=\log(91)[/tex]
[tex]3x=\frac{\log(91)}{\log(2)}[/tex]
[tex]x=\frac{\log(91)}{3\log(2)}[/tex]
[tex]x=2.169..[/tex]
Therefore, The solution of the equation is [tex]x=2.169..[/tex]
A taxi cab driver charges an initial flag drop fee of $2.75, plus $1.50 for each mile driven. Which equation models this situation if x= the number of miles driven and y=the total cost of a taxi ride?
[tex]\bf \begin{array}{llll} \stackrel{miles}{x}&\stackrel{cost}{y}\\ \cline{1-2} 0&2.75+1.50(0)&\leftarrow \textit{initial fee}\\ 1&2.75+1.50(1)\\ 2&2.75+1.50(2)\\ 3&2.75+1.50(3)\\ 4&2.75+1.50(4)\\ x&2.75+1.50(x)\\ \end{array}~\hspace{7em}\boxed{y=2.75+1.5x}[/tex]
if 3k is an even number integer which of the following cannot be an integer ?
A : k
B : k - 1
C : k/2
D : 3k
Answer:
c and a
because 3k has to add up the an even number so k by it self can not be an even number, and k/2 would still be an odd number because an off number divided by a even number still makes it odd
If 3k is an even integer then k is an even integer, and k and k - 1 are also integers. However, k/2 cannot be assured to be an integer unless k is a multiple of 4, making it the correct answer for what cannot be an integer.
If 3k is an even number, then k must also be an even number because an even number divided by 3 still leaves k as an integer. So, we can infer that k is an integer.
The option k - 1 must also be an integer because if k is an integer, subtracting 1 from it will result in another integer. The option 3k is given as an even integer, to begin with. However, the option k/2 cannot be an integer unless k is not only even but also a multiple of 4, because when you divide an even number that is not a multiple of 4 by 2, the result is not an integer.
Given the information provided in the question, we can conclude that k/2 is the option that cannot definitely be an integer without additional information specifying that k is indeed a multiple of 4.
Which algebraic expression represents "the difference of 54 and a number"?
[tex]\huge{\boxed{54-x}}[/tex]
The difference is the result of a subtraction problem.
We are given two values that are being subtracted: 54 and a number, represented by [tex]x[/tex]
So, represent this mathematically with [tex]\boxed{54-x}[/tex].
54-x is the correct answer, the difference between number is x-54 or 54-x and the number of algebraic expressions subtracted or number symbol like x.
What is the order of rotational symmetry for the figure
Answer:
4
Step-by-step explanation:
First of all we will define rotational symmetry.
Rotational symmetry is when a shape looks the same after some rotation or less than one rotation.
The order of rotational symmetry is how many times it matches the original shape during the rotation.
So for the given shape, we can observe that the shape has four same type of sides. The shape in rotation will be like original shape 4 times in a complete rotation. So the order of symmetry is 4 ..
Please help, math is my worst subject and I would really appreciate it!
Answer:
MW=CD
Step-by-step explanation: